Yield and yield components of wheat as affected by salinity and inoculation with Azospirillum strains from saline or non-saline soil - Somayeh Haji Nia; Mohammad Javad. Zarea; Farhad Rejali; A. Varma (Journal of the Saudi Society of Agricultural Sciences)
In many arid and semi-arid areas of the world where sustainability of agriculture is limited by salinity, use of biological potential may be a key component of sustainable plant production. A greenhouse experiment was used to test the effectiveness of inoculation with Azospirillum strains isolated from saline or non-saline soil in alleviating the salinity stress in wheat plants grown with irrigation water with different electrical conductivities (ECw) of 0.7, 4, 8 and 12 dS m−1. Inoculation with the two isolates increased salinity tolerance of wheat plants; the saline-adapted isolate significantly increased shoot dry weight and grain yield under severe water salinity. The component of grain yield most affected by inoculation was grains per plant. Plants inoculated with saline-adapted Azospirillum strains had higher N concentrations at all water salinity levels.